The Meaning of Polysemy in Political Reporting: A Semantic Study of the Gorontalo Bureau of ANTARA's National Newspaper - Sri Ratna Ruchban; Supriyadi; Salam (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe the form of polysemy (nouns, verbs, adjectives) in political news of LKBN Antara Gorontalo Bureau, describe its function in journalistic discourse, and reveal the nature of polysemy meaning as a relationship between lexical and contextual meaning in the Gorontalo election discourse community for the 2024-2025 period. Using a qualitative descriptive analysis approach with semantics, data was taken from 20 political news scripts on antaranews.com/gorontalo (November 2024-May 2025) covering the issues of the North Gorontalo PSU, election lawsuits, money politics, grant budgets, and election law enforcement. Data analysis follows the Miles & Huberman model with a semantic theory foundation. The results of the study identified 81 polysemy data with an unequal distribution: dominant nouns (68 data) such as “decision”, “stages”, “grant”, “lawsuit”, “rights”; verbs (11 data) such as “title”, “release”, “upload”; and adjectives only 2 data (“conducive”, “heavy”). These words undergo expansion, specialization, and transference of meanings typical of institutional election discourse. The function of polysemy encompasses three layers: linguistic economy and referential precision, subtle expressive-persuasiveness without violating neutrality, and educational-contextuality that activates readers’ knowledge of election regulations. The essence of its meaning consists of general lexical meaning and specific contextual meaning active in the election community. Polysemy is not ambiguity, but rather a systematic and efficient linguistic strategy for conveying complex information while maintaining journalistic objectivity. These findings confirm polysemy as a characteristic of regional election discourse and a potential teaching material for semantic learning, media literacy, and civic education.